Screening of Methicillin Resistant Staphylococcus aureus (MRSA) from Wounds in Pediatric Patients Visiting Tertiary Care in Hospital - Bhandari, Ganesh; Pokhrel, Basant; Oli, Yogesh; Katuwal, Archana; Bhandari, Netra Lal (Nepal Journal of Biotechnology, 2019)
The extent of methicillin-resistant Staphylococcus aureus (MRSA) in children is still unknown. The collected wound pus samples were processed. Identification of S. aureus was done according to standard microbiological procedures as per the clinical laboratory standards institute (CLSI) guidelines (2016). The antibiogram of the isolates was carried out by the Kirby-Bauer disc diffusion technique. MRSA was determined by measuring the zone of inhibition (ZOI) surrounding to cefoxitin disc, with resistance defined as ZOI of ≤ 21 mm. Out of 357 bacterial culture-positive samples, 278 (77.87 %) were S. aureus isolates, among them 102 (36.69%) were found to be MRSA. The percentage of MRSA isolates was found high in male children and inpatients with 61.76 % and 73.52% respectively. All the MRSA isolates were susceptible to gentamicin (79.41%), whereas (91.17%) were resistant to penicillin. The distribution of MRSA in inpatients 75 (73.52%) is higher than that of outpatients 27 (26.74%). This study shows that the MRSA occurrence is prevalent in pediatric patients.